Pengembangan Media Pembelajaran Fisika Berbasis Zoomable Presentation Berbantuan Software Prezi Pada Pokok Bahasan Listrik Dinamis - Robith Syaifullah Mahyuddin; Mustika Wati; Misbah Misbah (Berkala Ilmiah Pendidikan Fisika, 2017)
This research based on the need for the visualization of physics learning material that is both abstract and still uses conventional media in learning which have an impact on the motivation of students and the results of the study. In this research, researcher developed a physics learning media by using prezi software on dynamic electrical subject and has tested run at SMAN 1 Simpang Empat. The research purpose to produce a feasibility of physics learning media would be use in learning. As for the specific purpose of this research include: (1) describe the validity of learning media based on validation of media experts, (2) describe the practicallity of learning media from implementation of RPP, (3) describe the effectiveness of learning media based on cognitive learning results of students. The research was implemented by using the method of development research by the Dick and Carey design and the products developed is physics learning media based on zoomable presentation. The results showed: (1) the validity of the media learning valid categories by a few revision, (2) practicallity of media learning based on implementation of RPP is practical categories, and (3) the effectiveness of the learning media is rated with THB effective value. It was concluded that the physic learning media using prezi software to improve the learning results of prezi is feasible used in the learning process.